A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

Pollen-based response patterns of vegetation dynamics to environmental changes during the early-mid Holocene in the Ningshao Plain, China - Zhen Li; Chunmei Ma; Zijing She; Haiyan Li; Konglan Shao; Bin Zhou; Zhujun Hu; Qing Yang; Guoping Sun; Michael Meadows; Hongbo Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture” [Chem. Eng. J. 527 (2026) 171623] - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Aquatic biopeptides in flavor and metabolic regulation: A convergence of biochemistry and artificial intelligence - Haonan Sun; Tao Yu; Yuchen Zhang; Baosong Wang; Yuan Zhang; Weiqiang Qiu; Guoping Zhao; Yanbo Wang (Trends in Food Science & Technology, 2026)

Uncovering the role of Li+-H2O ion-dipole interaction in zeolite deactivation - Chenghao Liu; Yong Li; Zhe Lu; Shuzhuang Sun; Yong Wang; Zhifu Liu; Gang (Kevin) Li; Jingyue Shang; Songbai Hu; Lunhua He; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Assessment of the severity of lower extremity peripheral arterial disease based on gastrocnemius surface electromyography and mechanomyography signals - Wenxuan Sun; Yanbin Guo; Shuwei Lin; Guoping Wang; Youpeng Zhu; Yao Zhang; Ye Du; Zibo Feng (Medical & Biological Engineering & Computing, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Graphene light propulsion: experimental investigation, modeling, and potential application for deorbiting in low earth orbit - Haidong Zhu; Feng Sun; Tingwei Fu; Xiang Liu; Guoping Cai (Advances in Space Research, 2026)

Five daucane-type sesquiterpenes isolated from the roots of Ferula songarica Pall. ex Schult. and their anti-gastric cancer activity - Xiaotong Chang; Guoping Wang; Degang Qing; Yu Sun; Yaqin Zhao; Ning Lu; Leiling Shi; Jie Lv (Natural Product Research, 2026)

Combined aperture widening and strong polarization in Li+-exchanged mordenite for efficient direct air capture of CO2 - Zhifu Liu; Guanghui Shi; Shuzhuang Sun; Yong Wang; Jingyue Shang; Songbai Hu; Wenkang Deng; Chuhan Fu; Chenghao Liu; Xiao Wang; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Ocean dynamics in 2025: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Diego Bruciaferri; Sandro Carniel; Amin Chabchoub; W. Bryce Corlett; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Tsubasa Kodaira; et al. (Ocean Dynamics, 2026)

Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Compositional convergence of dissolved organic matter from root litter to rhizosphere soil in a semiarid grassland of North China - Xiaohan Mo; Zongxiao Zhang; Mengke Wang; Qiang Zhang; Guodong Sun; Weifeng Hu; Guoping Chen; Deliang Kong; Chengcheng Dong; Hui Zeng; Junjian Wang (Organic Geochemistry, 2025)

Design and synthesis of novel diamines for ultra low-temperature curable polyimides with enhanced copper adhesion - Jialin Tian; Xialei Lv; Wentao Wang; Jinhui Li; Jialin Zhang; Jie Liu; Chao Zhao; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2025)

Enhanced hydrological disturbance and atmospheric pollution on an ombrotrophic peatland (Greater Khingan Mountains, Northeast China) since 1950s inferred from diatom records - Dongxue Han; Yang Sun; Jinxin Cong; Guoping Wang; Chuanyu Gao (Anthropocene, 2025)

Geoarchaeological study of the evolution of rice farming fields in prehistoric Yangtze Delta and Huai River regions of China - Yijie Zhuang; Pin Ding; Lina Zhuang; Yonglei Wang; Wenwan Wu; Xia Wang; Yulong Niu; Guoping Sun; Xingtao Wei; Ling Qin (Quaternary Science Reviews, 2025)

Low-severity fire promote carbon emissions in permafrost peatlands of the Great Khingan Mountains, Northeast China - Guangxin Li; Long Sun; Shengzhen Ji; Xiao Li; Jinxin Cong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

A strategy for addressing large-scale hinge issues in large two-dimensional planar phased array antennas - Li Pei; Liu Xiang; Cai Guoping; Liu Fucheng; Sun Jun; Zhu Dongfang (Advances in Space Research, 2025)

Detrital zircon provenance record of the northern shelf in the Rakhine Basin, Bay of Bengal - Liangbo Ding; Hongxia Ma; Guozhang Fan; Xiaoyong Xu; Hongping Wang; Guoping Zuo; Ying Zhang; Hui Sun; Jianan Wu; Junmin Jia; Ming Su; Ce Wang (Marine and Petroleum Geology, 2025)

Synergy of Fe-modified zeolite and light stimulation on ammonia-stressed anaerobic digestion: Performance, microbial community and metabolic pathway - Zhiyuan Liu; Yunxin Zhu; Mingyuan Sun; Guangqi An; Jingwei Yang; Cheng Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2025)

Editorial– Ocean dynamics in 2024: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Pierre F. J. Lermusiaux; Zhiyu Liu; Yasumasa Miyazawa; et al. (Ocean Dynamics, 2025)

Ultra-sensitive and precisely decoupled pressure and temperature detection with a “soft-hard” asymmetrically structured sensor based on carbon-nanocoils - Yi He; Jian Zhang; Wei Xia; Dinghao Zhang; Yanming Sun; Guoping Wang; Qiang Zhang; Xiao Huang (Chemical Engineering Journal, 2024)

qSCR4.05 and qSCR4.08, two QTLs on chromosome 4 are associated with resistance to southern corn rust in maize - Junying Liu; Xiaoming Wang; Chenping Hou; Mingjian Hu; Wenjie Du; Pengfei Sun; Zhuangzhuang Dai; Xingchuan Wang; Ruijie Chen; Fei Gao; Guoping Shu; Yibo Wang; et al. (Physiological and Molecular Plant Pathology, 2024)

Distribution and response of electroactive microorganisms to freshwater river pollution - Shan Yang; Meijun Dong; Lizhou Lin; Bo Wu; Youda Huang; Jun Guo; Guoping Sun; Shaofeng Zhou; Meiying Xu (Environmental Pollution, 2024)

Early-mid Holocene vegetation and diversity evolution on the Ningshao Plain, eastern China - Zhen Li; Chunmei Ma; Yufan Ni; Zeyu Liu; Bingling Wang; Zhujun Hu; Guoping Sun; Yonglei Wang; Michael Meadows; Hongbo Zheng (CATENA, 2024)

Development of a sunlight adjustable parabolic trough reactor for 24-hour efficient photocatalytic wastewater treatment - Cheng Zhang; Guangqi An; Yunxin Zhu; Xiang Sun; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2024)

Halogen-functionalized covalent organic frameworks for photocatalytic Cr(VI) reduction under visible light - Dong Cao; Jian Guan; Jingcheng Du; Qian Sun; Ji Ma; Jingguo Li; Jiangtao Liu; Guoping Sheng (Journal of Hazardous Materials, 2024)

Integrated Metagenomics and 15N Isotope Tracing Reveal the Mechanisms Through which the Nitrogen-Planting Density Interaction Impacts Rice Root Nitrogen Uptake Efficiency - Changhui Sun; Yanyao Lu; Guoping Tang; Runnan Wang; Han Wu; Jiao Zhang; Shuo Cai; Jinyan Zhu; Qiangqiang Xiong (Journal of Soil Science and Plant Nutrition, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Feeding prehistoric coastal community: A study of marine faunal remains at the Jingtoushan site - Endong Wu; Guoping Sun; Ying Zhang (Science China Earth Sciences, 2024)

Editorial – Ocean Dynamics in 2023: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Richard J. Greatbatch; Pierre F. J. Lermusiaux; Zhiyu Liu; et al. (Ocean Dynamics, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

HvBGlu3, a GH1 β-glucosidase enzyme gene, negatively influences β-glucan content in barley grains - La Geng; Mengdi Li; Shanggeng Xie; Han Wang; Xinyi He; Nannan Sun; Guoping Zhang; Lingzhen Ye (Theoretical and Applied Genetics, 2024)

Explaining nitrogen turnover in sediments and water through variations in microbial community composition and potential function - Shan Yang; Meijun Dong; Huibin Lu; Zhipeng Cai; Meng Ge; Jia Xing; Haobin Huang; Youda Huang; Guoping Sun; Shaofeng Zhou; Meiying Xu (Chemosphere, 2023)

Photocatalytic degradation of multiple-organic-pollutant under visible light by graphene oxide modified composite: degradation pathway, DFT calculation and mechanism - Qiansu Ma; Jie Ming; Xiang Sun; Hongjian Zhang; Guangqi An; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Journal of Environmental Management, 2023)

A strategy to prepare low-temperature curable photosensitive polyimide with good comprehensive performance - Shan Huang; Xialei Lv; Xingwang Lai; Jinhui Li; Yao Zhang; Siyao Qiu; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The influence of cold filaments on the evolution of dipole structures - Qi Yang; Guihua Wang; Chi Xu; Guoping Gao; Ruili Sun (Frontiers in Marine Science, 2023)
Mesoscale eddy dipoles are oceanographic structures that can transport ocean water parcels horizontally and vertically in ways that differ from individual mesoscale eddies. The most conspicuous additional feature that presents in dipoles is the cold filament (CF) that can be spontaneously generated between a dipole’s anticyclonic eddy (AE) and cyclonic eddy (CE). A case study in this paper shows that the interaction between the CF and the CE component of the dipole is associated with the structural evolution of the dipole. This interaction is verified in synthesis and normalization studies of the CF dipoles. The CF-dipole interaction entrains CF water into the center of the dipole’ CE and leads to a cold and high chlorophyll center in the upper layer of the CE. The formation of this cold center changes the dipole’s structure by eliminating the phase difference between the thermal and dynamic centers of the dipole. The entrainment also provides a new mechanism for the development of high chlorophyll levels in the CE. In the analysis of the HYCOM (Hybrid Coordinate Ocean Model) simulation of a synthetic CF dipole, the AE has a three-zone structure while the CE only has two. The convergence of the CE’s outermost zone results in a biased interaction.

Development of a green and efficient photocatalytic mesh microalgae biorefinery (PMMB) system for sustainable biomass conversion under real solar light - Cheng Zhang; Jie Ming; Xiang Sun; Yunxin Zhu; Guangqi An; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2023)

Electrode materials for Li/Na storage from mechanochemically synthesised MOFs/MXene Composites: A Solvent-free approach - Xiaoyan Shi; Weiquan Liang; Guoping Liu; Bin Chen; Lianyi Shao; Yanxue Wu; Zhipeng Sun; Felipe García (Chemical Engineering Journal, 2023)

Advanced photocatalytic sterilization for recalcitrant Enterococcus sp. contaminated water by newly developed Z-scheme Bi2WO6 based composites under solar light - Jie Ming; Xiang Sun; Qiansu Ma; Na Liu; Cheng Zhang; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Chemosphere, 2023)

Complexing agents-free bioelectrochemical trickling systems for highly-efficient mesothermal NO removal: The role of extracellular polymer substances - Xingzhu Huang; Shaofeng Zhou; Jianjun Li; Xiaojun Wang; Shaobin Huang; Guoping Sun; Shan Yang; Jia Xing; Meiying Xu (Bioresource Technology, 2023)

Ecological distribution of modern diatom in peatlands in the northern Greater Khingan Mountains and its environmental implications - Dongxue Han; Yang Sun; Jinxin Cong; Chuanyu Gao; Guoping Wang (Environmental Science and Pollution Research, 2022)

Effect of maternal thallium exposure in early pregnancy on the risk of preterm birth - Xi Chen; Li Huang; Qian Li; Xu Zhang; Xiaoyi Wang; Guoqiang Sun; Nianhua Yi; Guoping Xiong; Xuefeng Yang; Liping Hao; Hongying Yang; Nianhong Yang (Environmental Science and Pollution Research, 2022)

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Typha as a wetland food resource: evidence from the Tianluoshan site, Lower Yangtze Region, China - Yunan Zhang; Bas van Geel; William D. Gosling; Guoping Sun; Ling Qin; Xiaohong Wu (Vegetation History and Archaeobotany, 2020)

Were chickens exploited in the Neolithic early rice cultivation society of the lower Yangtze River? - Masaki Eda; Hiroki Kikuchi; Guoping Sun; Akira Matsui (Archaeological and Anthropological Sciences, 2019)

Comparison of two air temperature gridding methods over complex terrain in China - Guoping Shi; Zhian Sun; Xinfa Qiu; Yan Zeng; Peng Chen; Changjie Liu (Theoretical and Applied Climatology, 2018)

Impact of polar lows on synoptic scale variability of Atlantic inflow in the Fram Strait - Ruili Sun; Guoping Gao (Acta Oceanologica Sinica, 2018)

Modification of the SUNFLUX solar radiation scheme with a new aerosol parameterization and its validation using observation network data - Yongjian He; Zhi’an Sun; Guoping Shi; Jingmiao Liu; Jiandong Li (Advances in Atmospheric Sciences, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Holocene range collapse of giant muntjacs and pseudo‐endemism in the Annamite large mammal fauna - Samuel T. Turvey; James Hansford; Selina Brace; Victoria Mullin; Shengxiao Gu; Guoping Sun (Journal of Biogeography, 2016)
Aim To clarify the post‐glacial biogeography of the Annamite and eastern Chinese ungulate faunas, and determine whether current understanding of Asian mammalian biogeography is biased by pseudo‐extinctions and pseudo‐endemism associated with a historical extinction filter. Location Modern‐day specimens of giant muntjac ( Muntiacus vuquangensis ) from the Annamite Mountains of Laos and Vietnam were compared with zooarchaeological specimens of extinct giant muntjac ( M. gigas ) from eastern China, and with a reference sample of northern red muntjac ( M. vaginalis ) from China, Southeast Asia and South Asia. Methods We analysed a data set of antler measurements using Multivariate analyses of variance ( MANOVA s), principal component analyses ( PCA s) and scaling relationships, to quantify morphometric variation between extinct and living giant muntjacs in relation to variation shown by a different sympatric large‐bodied muntjac species. We also attempted ancient biomolecule analysis of Holocene samples from China. Results Although the combined giant muntjac sample can be differentiated from the reference red muntjac sample in all of our multivariate morphometric analyses, no significant differences are shown between extinct and living giant muntjacs using any analyses, matching the pattern seen when comparing conspecific red muntjac samples from across the same geographical region. Main conclusions We find no support for recognizing extinct and living giant muntjacs as distinct taxa, and post‐glacial populations from China and the Annamites should probably all be referred to M. gigas . The likely conspecificity of giant muntjacs across Eastern and Southeast Asia demonstrates that current‐day Asian mammalian biogeography has been shaped by an extinction filter and challenges the idea that the Annamite region represents a cradle of evolution; instead, it may represent a refuge of diversity for some taxa, preserving remnant pseudo‐endemic populations of species that have been extirpated across other parts of their former ranges.

Statistical characteristics and formation mechanism of the Lanyu cold eddy - Ruili Sun; Yanzhen Gu; Peiliang Li; Lei Li; Fangguo Zhai; Guoping Gao (Journal of Oceanography, 2016)

Viral metagenomics analysis of picobirnavirus-positive feces from children with sporadic diarrhea in China - Guangming Sun; Qinbo Zang; Yu Gu; Guoping Niu; Chen Ding; Peiying Zhang (Archives of Virology, 2016)

Wogonin Protects Rat Dorsal Root Ganglion Neurons Against Tunicamycin-Induced ER Stress Through the PERK-eIF2α-ATF4 Signaling Pathway - Fangyi Chen; Rongbo Wu; Zhu Zhu; Wangping Yin; Min Xiong; Jianwei Sun; Miaozhong Ni; Guoping Cai; Xinchao Zhang (Journal of Molecular Neuroscience, 2015)

Effects of industrial relocation on Chinese regional economic growth disparities: Based on system dynamics modeling - Aizhi Wu; Guoping Li; Tieshan Sun; Yusheng Liang (Chinese Geographical Science, 2014)

Mapping the Time Course of Other-Race Face Classification Advantage: A Cross-Race ERP Study - Gang Sun; Guoping Zhang; Yanjie Yang; Shlomo Bentin; Lun Zhao (Brain Topography, 2014)

Synergistic degradation of deca-BDE by an enrichment culture and zero-valent iron - Xingjuan Chen; Guilan Chen; Mengde Qiu; Guoping Sun; Jun Guo; Meiying Xu (Environmental Science and Pollution Research, 2014)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

Suburbanization and subcentering of population in Beijing metropolitan area: A nonparametric analysis - Tieshan Sun; Zhenhai Han; Lanlan Wang; Guoping Li (Chinese Geographical Science, 2012)

Effects of electron donors on anaerobic microbial debromination of polybrominated diphenyl ethers (PBDEs) - Mengde Qiu; Xingjuan Chen; Daiyong Deng; Jun Guo; Guoping Sun; Bixian Mai; Meiying Xu (Biodegradation, 2012)

Performance of a biotrickling filter in the removal of waste gases containing low concentrations of mixed VOCs from a paint and coating plant - Jianjun Li; Guangyun Ye; Duanfang Sun; Taicheng An; Guoping Sun; Shizhong Liang (Biodegradation, 2012)

Association between the IL7R T244I polymorphism and multiple sclerosis: a meta-analysis - Ruijie Zhang; Lian Duan; Yongshuai Jiang; Xuehong Zhang; Peng Sun; Jin Li; Mingming Zhang; Guoping Tang; Xing Wang; Xia Li (Molecular Biology Reports, 2011)

Effects of Cadmium, Chromium and Lead on Growth, Metal Uptake and Antioxidative Capacity in Typha angustifolia - Alieu Mohamed Bah; Huaxin Dai; Jing Zhao; Hongyan Sun; Fangbin Cao; Guoping Zhang; Feibo Wu (Biological Trace Element Research, 2011)

Genotype-Dependent Effect of Exogenous Nitric Oxide on Cd-induced Changes in Antioxidative Metabolism, Ultrastructure, and Photosynthetic Performance in Barley Seedlings (Hordeum vulgare) - Fei Chen; Fang Wang; Hongyan Sun; Yue Cai; Weihua Mao; Guoping Zhang; Eva Vincze; Feibo Wu (Journal of Plant Growth Regulation, 2010)

Paleosalinity in the Tianluoshan site and the correlation between the Hemudu culture and its environmental background - Minglin Li; Duowen Mo; Longjiang Mao; Guoping Sun; Kunshu Zhou (Journal of Geographical Sciences, 2010)

The fluxes and controlling factors of N2O and CH4 emissions from freshwater marsh in Northeast China - JunBao Yu; JingShuang Liu; ZhiGao Sun; WeiDong Sun; JinDa Wang; GuoPing Wang; XiaoBing Chen (Science China Earth Sciences, 2010)

Difference in response to drought stress among Tibet wild barley genotypes - Jing Zhao; Hongyan Sun; Huaxin Dai; Guoping Zhang; Feibo Wu (Euphytica, 2010)

In vitro antimicrobial activity of the leaf essential oil of Spiraea alpina Pall. - Yun Teng; Qian Yang; Zhiyi Yu; Guoping Zhou; Qiu Sun; Hong Jin; Taiping Hou (World Journal of Microbiology and Biotechnology, 2010)

Characterization of Bombyx mori parvo-like virus non-structural protein NS1 - Guohui Li; Chen Sun; Junhong Zhang; Yuanqing He; Huiqing Chen; Jie Kong; Guoping Huang; Keping Chen; Qin Yao (Virus Genes, 2009)

Spermatogenesis-related ring finger gene ZNF230 promoter: identification and functional analysis - Wenming Xu; Sizhong Zhang; Weimin Qiu; Guoping He; Yunqiang Liu; Yan Sun; Yongxin Ma; Jingtao Dong; Wei Zhang (Molecular Biology Reports, 2009)

Microbial Metabolism of Quinoline by Comamonas sp. - Mingchao Cui; Fanzhong Chen; Jiamo Fu; Guoying Sheng; Guoping Sun (World Journal of Microbiology and Biotechnology, 2004)